2006
DOI: 10.1093/jxb/erj097
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of 1-aminocyclopropane-1-carboxylic acid synthase isogene, Pp-ACS1, in peach fruit softening

Abstract: Ethylene promotes fruit ripening, including softening. The fruit of melting-flesh peach (Prunus persica (L). Batsch) cultivar 'Akatsuki' produces increasing levels of ethylene, and the flesh firmness softens rapidly during the ripening stage. On the other hand, the fruit of stony hard peach cultivars 'Yumyeong', 'Odoroki', and 'Manami' does not soften and produces little ethylene during fruit ripening and storage. To clarify the mechanism of suppression of ethylene production in stony hard peaches, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 29 publications
2
56
1
Order By: Relevance
“…This ethylene increase did not correlate with PpACO1 content (Figure 8C). It is known that the main regulatory step in the ethylene synthesis in peaches is related to the Prunus persica 1-aminocyclopropane-1-carboxylate synthase 1 (PpACS1) transcriptional and/or translational control [64]. However, we did not identify PpACS1 in this study and therefore cannot rule out the possibility that the ethylene increase observed in the E4 stage is associated to this protein.…”
Section: Discussionmentioning
confidence: 73%
“…This ethylene increase did not correlate with PpACO1 content (Figure 8C). It is known that the main regulatory step in the ethylene synthesis in peaches is related to the Prunus persica 1-aminocyclopropane-1-carboxylate synthase 1 (PpACS1) transcriptional and/or translational control [64]. However, we did not identify PpACS1 in this study and therefore cannot rule out the possibility that the ethylene increase observed in the E4 stage is associated to this protein.…”
Section: Discussionmentioning
confidence: 73%
“…Several of these differentially expressed genes are likely involved in terpene and gibberellin synthesis, ethylene production and signaling, cell-wall remodeling, cell division and defense responses (Additional file 1). In particular, we noticed that the ethylene synthesis pathway represented by orthologs of ACC synthase, ACC oxidase and AP2 factor genes, which play roles in cell wall softening [32-34], appears to be a primary mechanism elicited in the host after Xc sensing. On the other hand, defense response genes encoding chitinases, WRKY factors and pathogenesis-related (PR) proteins are also rapidly induced (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that in the stony hard peach, ACC oxidase activity and ethylene sensing are normal, and endogenous ethylene production is inhibited due to the inability to synthesize ACC. To clarify the suppression mechanism of ethylene production in the stony hard peaches, Tatsuki et al examined the expression levels of ACC synthases (Pp-ACS1, Pp-ACS2, and Pp-ACS3) and ACC oxidase (Pp-ACO1) in melting and stony hard cultivars 18 . They concluded that inhibition of endogenous ethylene production in the stony hard peach fruit was due to the suppressed expression of Pp-ACS1 mRNA.…”
Section: Disciplinementioning
confidence: 99%